Global talent management - Farndale, Elaine (Henry Stewart Talks, 2011)
Human resource management, Staffing flows, High-potential employees, High-performing employees, Talent pool, War for talent, Talent supply and demand, Self-initiated movers, Global mobility, Skill shortages, Talent retention, Silo mentalities, Global staffing, Champion of processes, Guardian of culture, Managers of internal receptivity, Network leadership, Local responsiveness, Employer branding
Updated at 2017/04/30